Fluorophores, environments, and quantification techniques in the analysis of transmembrane helix interaction using FRET. Issue 4 (July 2015) - Khadria, Ambalika S.; Senes, Alessandro
ABSTRACT: Förster resonance energy transfer (FRET) has been widely used as a spectroscopic tool in vitro to study the interactions between transmembrane (TM) helices in detergent and lipid environments. This technique has been instrumental to many studies that have greatly contributed to quantitative understanding of the physical principles that govern helix–helix interactions in the membrane. These studies have also improved our understanding of the biological role of oligomerization in membrane proteins. In this review, we focus on the combinations of fluorophores used, the membrane mimetic environments, and measurement techniques that have been applied to study model systems as well as biological oligomeric complexes in vitro. We highlight the different formalisms used to calculate FRET efficiency and the challenges associated with accurate quantification. The goal is to provide the reader with a comparative summary of the relevant literature for planning and designing FRET experiments aimed at measuring TM helix–helix associations. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 247–264, 2015.